2021
DOI: 10.21203/rs.3.rs-56843/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characteristics of refractory Mycoplasma pneumoniae pneumonia in children treated with glucocorticoid pulse therapy

Abstract: Background: To observe the effect of corticosteroids in the treatment of children with refractory Mycoplasma pneumoniae pneumonia(RMPP) under different doses, to summarize the clinical features of children treated with glucocorticoid pulse therapy.Methods: The clinical data of 125 children with RMPP hospitalized in Tianjin Children's Hospital from September 2018 to October 2019 were retrospectively analyzed. They were divided into two groups according to the dose of hormone. Compare the clinical features, labo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Some biomarkers linked to in ammatory reactions had been used to predict RMPP by previous studies 21,26 . The peak temperature in the RMPP group was signi cantly higher than that in the CMPP group on the rst day of admission 27 . These markers were higher in the RMPP group than in the CMPP group, implying that children with refractory M. pneumoniae pneumonia have more pronounced in ammatory responses.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Some biomarkers linked to in ammatory reactions had been used to predict RMPP by previous studies 21,26 . The peak temperature in the RMPP group was signi cantly higher than that in the CMPP group on the rst day of admission 27 . These markers were higher in the RMPP group than in the CMPP group, implying that children with refractory M. pneumoniae pneumonia have more pronounced in ammatory responses.…”
Section: Discussionmentioning
confidence: 77%
“…After an MP infection, hepatic impairment is common extrapulmonary damage 21 . The study showed that the AST in the RMPP group was higher 27 .…”
Section: Discussionmentioning
confidence: 88%